2016
DOI: 10.3354/dao02990
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues affecting the study of fish parasites. I. Duration of live fish storage prior to dissection

Abstract: We tested the ability of parasite species to respond quickly to artificial conditions (e.g. by changing abundance or even decreasing to extinction) while host fish species were being held alive prior to dissection. Prussian carp Carassius gibelio were sampled by electrofishing from 2 ponds alongside the River Dyje (Czech Republic) during 'cold' and 'warm' seasons. All fish were transported to the laboratory in aerated pond water and kept in a 1 m 3 outdoor basin with aged tap water for 6 d. Twenty fish were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 30 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…Trichodina sp. occur at high abundance in warmer waters (Kvach, Ondračková, et al, 2016), thus they were only recorded in Ukraine and not Latvia, where they are likely to be rare due to the colder climate. Another possible reason of the absence of Trichodina sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichodina sp. occur at high abundance in warmer waters (Kvach, Ondračková, et al, 2016), thus they were only recorded in Ukraine and not Latvia, where they are likely to be rare due to the colder climate. Another possible reason of the absence of Trichodina sp.…”
Section: Discussionmentioning
confidence: 99%
“…In Ukraine, fish were taken from two sampling sites on the Danube delta, Lake Kartal (45.287011N, 28.518269E) Table 1) using either a 10-m beach seine (6-mm mesh) or a 0.5-m long dipnet (0.5-cm mesh) in the vegetation zone (depth 1-m). All fish were placed into canisters filled with the aerated local water and immediately transported to the laboratory, where they were examined for parasites within 48 hr of catching (see Kvach, Ondračková, Janáč, & Jurajda, 2016). Both standard (SL) and total (TL) length of each fish was measured before section, following which the fins, skin, gills, eyes, muscles, viscera and internal organs (gut, liver, gall bladder, spleen, swimming bladder, kidneys, uterine bladder, gonads, mesentery and brain) were examined for parasites.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…Th e fi sh were dissected within 48 hrs. as recommended by Kvach et al (2016). Th e digeneans were isolated from the gut, washed in saline and fi xed with hot 4% formalin (Cribb & Bray, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…All fish were sampled using electrofishing and transported alive to the Institute of Vertebrate Biology of the Academy of Sciences of the Czech Republic (Brno, Czech Republic) in aerated barrels. The fish were kept alive in two outdoor basins (fish from the two different localities separated) and dissected within 3 days of collection (see Kvach et al , 2016b).…”
Section: Methodsmentioning
confidence: 99%
“…First, preserving fish in ethanol could result in loss of some parasite species or problems with identification (Zander, 2004). More recent studies have shown that keeping fish alive until needed for parasitological dissection greatly improves the accuracy of parasitological community determination (Kvach et al , 2016b). Second, as the Chinese sleeper matures at around 6 cm (Kottelat & Freyhof, 2007); the 2–4 cm size group used in the study clearly represents immature 0+ specimens.…”
Section: Introductionmentioning
confidence: 99%